2016
DOI: 10.1108/bij-12-2014-0112
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the linkage between Organizational Culture and TQM

Abstract: Purpose – The purpose of this paper is to examine the impact of Organisational Culture (OC) on total quality management (TQM) implementation in Indian small and medium enterprises (SMEs) in the auto component sector. Specifically; it attempts to propose a model linking OC and TQM for this sector. Design/methodology/approach – Survey method was used for data collection by targeting the whole population of 482 Indian auto component SMEs dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 48 publications
4
27
0
1
Order By: Relevance
“…In the same way, the relationship between TQM and OC shows a significant effect at the 0.001 significance level (B = 0.65; t = 13.27; p < 0.001), and thus H2 is supported. this finding is consistent with previous studies which reveal a positive association between TQM and OC based on the CVF (Sinha et al., 2016; Valmohammadi and Roshanzamir, 2015). This means that firms should be paying more attention to providing a supportive OC in order to achieve successful implementation of TQM.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…In the same way, the relationship between TQM and OC shows a significant effect at the 0.001 significance level (B = 0.65; t = 13.27; p < 0.001), and thus H2 is supported. this finding is consistent with previous studies which reveal a positive association between TQM and OC based on the CVF (Sinha et al., 2016; Valmohammadi and Roshanzamir, 2015). This means that firms should be paying more attention to providing a supportive OC in order to achieve successful implementation of TQM.…”
Section: Resultssupporting
confidence: 94%
“…The findings of this research provided empirical evidence for the suggested concepts of TQM, OC and performance of SMEs as reflective second-order constructs. This procedure is consistent with previous research (Calvo-Mora et al., 2014; Kanapathy et al., 2017; Sinha et al., 2016). Moreover, the research aim is to examine the effect of TQM and OC as one single construct to better understand how they influence other variables.…”
Section: Resultssupporting
confidence: 93%
“…Encouraging trial ability and creativity are mentioned as amongst the basic elements of QM (Guimaraes, 1996;Mosadeghrad, 2015). Trial ability is the degree to which an innovation can be experimented (Sinha et al, 2016). Through experimentation, employees' can try out novel ways of handling problems in their organization.…”
Section: Trial Ability and Innovationmentioning
confidence: 99%
“…This helps employees' work more effectively. With openness, employees' can share their ideas without the fear of being ridiculed and are not defensive about it (Sinha et al, 2016).…”
Section: Trial Ability and Innovationmentioning
confidence: 99%
“…In general, their research is intended to discover obstacles to the successful implementation of TQM and the effect of the application of TQM on organizational performance. In this study, TQM as a management system is considered to be well recognized by many parties and the focus of research is to discover how effective the application of TQM systems in a company by using the ISO 9001: 2015 quality management system approach [4]. The previous studies more emphasis on success and obstacles in the application of TQM by studying the application of TQM using a very varied method.…”
Section: Introductionmentioning
confidence: 99%